The Relationship Of Quality Management Supervision To Job Satisfaction Of Inpatient Nurses In Hospital "Ah" - Fera Elmiati (Jurnal Indonesia Sosial Teknologi, 2023)
Job satisfaction is the general attitude of an individual person towards the work he does. Someone with a high level of job satisfaction shows a positive attitude towards their job, while someone who is dissatisfied with their job shows a negative attitude towards their job. High job satisfaction is a sign that the organization has carried out effective behavior management. Supervisory Management or Supervision Management is the process carried out by the supervision executor in supervising and directing, and striving to foster and improve the ability of the supervised party in order to carry out the tasks that have been given efficiently and effectively. The quality of supervision and good supervisors significantly and positively affects job satisfaction, the quality of supervisors greatly determines high job satisfaction. Research Objective: want to know whether there is a relationship between the quality of supervision management by supervisors with nurse satisfaction in hospital "AH". Method: quantitative research using cross sectional approach method. Data collection techniques are carried out by collecting primary data, namely by using questionnaires given through Google Form to respondents. Research Results: there is a significant relationship between the quality of supervision management and the job satisfaction of nurses at Hospital "AH" Conclusion: The better the quality of supervision management, the higher the level of job satisfaction of nurses at Hospital "AH". Suggestions: make a strategy plan for improving the quality of supervision management, selection of supervisors and training supervisors